Brain Cholinergic Function and Response to Rivastigmine in Patients With Chronic Sequels of Traumatic Brain Injury: A PET Study. Issue 1 (January 2018) - Östberg, Anna; Virta, Jere; Rinne, Juha O.; Oikonen, Vesa; Luoto, Pauliina; Någren, Kjell; Arponen, Eveliina; Tenovuo, Olli
Abstract : Objective: To investigate quantitative positron emission tomography (PET) findings and to study whether the cholinergic function differs between respondents to cholinergic medication versus nonrespondents. Setting: Outpatient clinic and university PET imaging center. Participants: We studied 17 subjects for more than 1 year after at least moderate traumatic brain injury. Ten of the subjects were respondents and 7 nonrespondents to cholinergic medication. Design: Cholinergic function was assessed with [methyl- 11 C] N -methylpiperidyl-4-acetate-PET ( 11 C-MP4A-PET), which reflects the activity of the acetylcholinesterase (AChE) enzyme. The subjects were PET scanned twice: without medication and after a 4-week treatment with rivastigmine 1.5 mg twice a day. Measures: Regional cerebral AChE activity was measured with PET. Results: At baseline Statistical Parametric Mapping analyses showed significantly lower AChE activity in respondents bilaterally in the frontal cortex as compared with nonrespondents. Region of interest (ROI) analysis revealed that the difference was most pronounced in the lateral frontal cortex (−9.4%, P = .034) and anterior cingulate (−6.0%, P = .049). After rivastigmine treatment, AChE activity was notably lower throughout the cortex in both respondents and nonrespondents, without significant differences between them. Conclusion: Our study suggests that frontal cholinergic dysfunction is associated with the clinical response to cholinergic stimulation in patients with traumatic brain injury.